2012
DOI: 10.2147/ijn.s34773
|View full text |Cite
|
Sign up to set email alerts
|

pH-sensitive strontium carbonate nanoparticles as new anticancer vehicles for controlled etoposide release

Abstract: Strontium carbonate nanoparticles (SCNs), a novel biodegradable nanosystem for the pH-sensitive release of anticancer drugs, were developed via a facile mixed solvent method aimed at creating smart drug delivery in acidic conditions, particularly in tumor environments. Structural characterization of SCNs revealed that the engineered nanocarriers were uniform in size and presented a dumbbell-shaped morphology with a dense mass of a scale-like spine coating, which could serve as the storage structure for hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Such pH gradients have been exploited for the conception and development of pH-responsive nanomaterials that can release bioactive compounds without any external trigger 37 . Carbonate systems have been of particular interest for being biodegradable, nontoxic to normal cells and present a cumulative drug release in acid-dependent systems 38 along with their use as carriers to encapsulate and adsorb bioactive compounds 39 40 . Other interesting features have been observed for calcium carbonate particles, such as their application as micropumps by using differently charged particles as tracers to show the diffusioosmotic flows arising in an unsaturated aqueous solution 41 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such pH gradients have been exploited for the conception and development of pH-responsive nanomaterials that can release bioactive compounds without any external trigger 37 . Carbonate systems have been of particular interest for being biodegradable, nontoxic to normal cells and present a cumulative drug release in acid-dependent systems 38 along with their use as carriers to encapsulate and adsorb bioactive compounds 39 40 . Other interesting features have been observed for calcium carbonate particles, such as their application as micropumps by using differently charged particles as tracers to show the diffusioosmotic flows arising in an unsaturated aqueous solution 41 .…”
mentioning
confidence: 99%
“…Carbonate-based microstructures were successfully applied for cargo loading and delivery in presence of acidosis metabolism 38 , encouraging us to exploit such material as biocompatible micromotors with the potential for directed drug delivery. Here we implement this concept by the synthesis and characterization of novel biocompatible and biodegradable asymmetric Janus motors, which move in the presence of extremely light acidic conditions attributed to tumorous growth (see Fig.…”
mentioning
confidence: 99%
“…Figure 5 shows the absence of any new peaks in the physical mixture, and all characteristic peaks of ETO, EC, and ET-ETO appeared without any significant shift, indicating the absence of chemical drug-polymer interactions in the solid state. Qian et al and Patel et al showed the same results for different ETO polymers [33,34]. The physical stability of the prepared microparticles with and without ETO was confirmed by storage of the prepared microparticles for two months at 25 • C and 4 • C. The results showed no change in colour, shape, particle size diameter, or drug content before and after storage.…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 59%
“…7 Apart from CaCO 3 , iron carbonate (FeCO 3 ) NPs have recently been produced and used as magnetic resonance contrast agents to track in vivo malignancies, with substantial biocompatibility and contrast properties. 8 Despite their potential benefits, metal carbonates are currently limited to calcium (Ca), magnesium (Mg), iron (Fe), barium (Ba), 9,10 and strontium (Sr) 11 On the other hand, the application of nanomaterials as nanozymes has gained tremendous attention due to their unique structural, electrical, and optical properties, as well as remarkable catalytic activities. 12 Nanozymes have several advantages over natural enzymes, including their stability, low cost, and ease of synthesis.…”
Section: Introductionmentioning
confidence: 99%